Influenza-Associated Medical Visits Prevented by Influenza Vaccination in Young Children in Thailand, 2012–2014. (24th July 2020) - Rolfes, Melissa A; Olsen, Sonja J; Kittikraisak, Wanitchaya; Suntarattiwong, Piyarat; Klungthong, Chonticha; Ellison, Damon; Mott, Joshua A; Chotpitayasunondh, Tawee
Abstract: Despite recommendations, few children aged 6–35 months in Thailand receive seasonal influenza vaccination. Using previously estimated incidence and vaccine effectiveness data from the period 2012–2014, we estimate that up to 121 000 medical visits could be prevented each year with 50% coverage and expanded recommendations to children aged <5 years.